(untitled) (Canadian Journal of Native Studies, 2026)
Abstract The underfunding of First Nations K-12 education in Canada has created a disparity in the quality of education received by First Nations students compared to non-First Nations students. Understanding the connection between funding and student outcomes might prove useful in confronting this disparity. Additional funding will not resolve all education problems, so those evaluating funding and policy interventions would benefit from considering factors such as efficiency, effectiveness, equity and the social context of learning. To create social change and understand if policy is a suitable tool for intervention, it is helpful to understand why the gap in education exists. If the gap does result in disparity of education outcomes, it is a worthwhile subject to explore. In this case, the gap is suggested to affect student outcomes and Indigenous communities and organizations have reiterated this to the federal government (Assembly of First Nations, 2017).